Satcom on the move (SOTM) terminals evaluation under realistic conditions - Alazab, Mostafa; Del Galdo, Giovanni; Felber, Wolfgang; Heuberger, Albert; Lorenz, Mario; Raschke, Florian; Siegert, Gregor; Landmann, Markus (IEEE Vehicular Technology Conference, 2013)
The Vehicle-Mounted Earth Stations (VMES) operation requirements defined by the regulatory authorities are bounding for terminal manufacturers. Testing the VMES for these requirements (e.g., pointing accuracy and polarization alignment) is therefore a necessity. The disadvantages of involving operational satellites and having fixed separation between them in traditional test methods are overcome in the proposed Facility for Over-the-air Research and TEsting (FORTE). FORTE comprises an antenna tower and a laboratory building. A sensor array is mounted on the antenna tower with the center sensor emulating the satellite. In the laboratory building, the VMES is mounted on a motion emulator which can replay realistic motion profiles. In this contribution, the main components of FORTE are introduced and the performance of the de-pointing measurement system is verified. The tracking unit of the VMES may steer the antenna either mechanically or electronically to keep the pointing direction towards the target satellite. Measurements with antennas that have a fixed pattern (independent of the steering angle) as well as that have a variable pattern (dependent on the steering angle) are considered in this contribution. © 2013 IEEE.
CRIS-Team Scopus Importer:2025-11-10
Keywords: De-pointing measurement; ETSI EN 302977; FCC 25.226; Ka band; Ku band; LMS channel; Mobile VSAT; Motion profiles; SOTM; VMES